Eco-efficient value creation of Cork Products: an LCA-based method for Design Intervention (Journal of Cleaner Production, 2013)
Cork, a natural, recyclable, non-toxic and renewable resource, which stems from the bark of a cork oak in the Mediterranean cork forest (Montado), is an excellent material for Sustainable Product Design. This article describes a project, developed for the Portuguese Cork Industry, on the sustainable innovation of cork products, using the method of “Design Interventions” for new product development, combined with the method of “Eco-efficient Value Creation”. Design Intervention is a method to generate innovative products in a structured way with a team of designers, focussing on maximum customer perceived value. The method has four levels: project strategic level, concept development level, design implementation level and product diffusion level. It includes workshops, combined with work in the design studios of the individual designers. The design concepts are analysed with respect to sustainability, and the market value of the prototypes are tested. Eco-efficient value creation is LCA based method with a double objective: 1. reduce the eco-burden of a product (and/or service), and at the same time, 2. enhance the customer perceived value. In this method, the combination of customer perceived value and eco-burden of the product is optimised, aiming at a high level of eco-effectiveness. The eco-burden is determined by means of Life Cycle Assessment (according to ISO 14040/44). The customer perceived value is determined by the price of the product in the market. The project showed that this two dimensional approach, generated good results: 27 out of the 36 new designs ended up with better characteristics (lower eco-costs at a higher value) than their reference products. Products have been exhibited in several international cities, and are sold in design shops